Clinical management of the first ASCUS report in Chile.: Prospective single-cohort study - ópez-Alegría, Fanny; Quezada Poblete, Orlando; De Lorenzi, Dino Soares; Sepúlveda Oyanedel, Juan Carlos (São Paulo Medical Journal, 2015)
CONTEXT AND OBJECTIVE: Worldwide, there is no single strategy for optimal management of patients with ASCUS (atypical squamous cells of undetermined significance) cytology reports. The objective of this study was to determine the kind of clinical management conducted among women with a first ASCUS Pap smear report. DESIGN AND SETTING: Prospective single cohort study at a cervical pathology unit in Santiago, Chile. METHODS: This was an epidemiological, descriptive, observational and quantitative follow-up study on a cohort of women with ASCUS cytological reports. RESULTS: In the screening phase, 92,001 cervical cytological smears were collected in primary healthcare clinics. In the diagnostic phase, all women with a first ASCUS report were selected (n = 446). These women were asked to undergo the Pap test again and it was found that 301 women had normal results, 62 women had abnormal results and 83 did not repeat the test. In the diagnostic confirmation phase, the 62 women with abnormal results underwent colposcopy and, from these results, 58 of them underwent a biopsy. The results from the biopsies showed that 16 women had negative histological reports, 13 had CIN 1 and 29 had CIN 2+. In the treatment phase, the 42 women with lesions underwent a variety of treatments, according to the type of lesion. In the post-treatment phase, cytological and colposcopic monitoring was instituted. CONCLUSION: The clinical management consisted of traditional management of screening, diagnosis, diagnostic confirmation, treatment and post-treatment monitoring.